Pengaruh Relaxation Music Therapy (RMT) Pada Kecemasan Akademik - Akmal Sutja; Rully Andi Yaksa (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
This study aimed to evaluate the effect of relaxation music therapy (RMT) to reduce academic anxiety before carrying out the final academic exam. The type of this research is Pre-Experiment with one group pretest-posttest design. The subjects in this study were 51 final year students preparing for their final academic examinations at Universitas Jambi, using purposive sampling. The instrument used was an anxiety scale. Data analysis used nonparametric statistical techniques using the Wilcoxon Signed-Ranks Test and the Rasch Model. The results show that there is an effect of RMT to reduce academic anxiety of final year students at Universitas Jambi. Furthermore, the ability of students to respond to the pretest was still in anxious condition which resulted in the results of the pretest being still moderate (mean measure = 0.04 logit). In contrast, when RMT has been given treatment, the student's ability to respond to the posttest has become low (mean measure = -0.49 logit). These findings could be used by counselors to reduce academic anxiety of final year students at the University and the implications of guidance and counseling are discussed further.